ANALISIS PEMBERDAYAAN MASYARAKAT MUSLIM MISKIN MELALUI QARDUL HASAN (Studi kasus Program Baitul Maal BMT Beringharjo Yogyakarta Tahun 2013) - Hardi, Eja Armaz (Jurnal Ekonomi Islam, 2014)
The issue of poverty is still a important case in Indonesia. Various programs held to decrease the number of poverty. One of these programs is qardhul hasan. Baitul Maal (BM) Baitul Maal wa Tamwil (BMT) Beringharjo conduct the empowerment of muslim society by qardhul hasan program called Sahabat Ikhtiar Mandiri (SIM) which utilize funds from Zakat, Infaq, Sedekah dan Wakaf (ZISWA). This research aims to analyze the variables which supposed affecting the success of this program to increase the customerâs oncome and to analyze their income and shadaqa before and after following this program. This research used four independent variables; duration of program, mentoring quality, duration of office hour and shadaqa. It also used a dependent variable; it is the increase of income. At independent variable âmentoring qualityâ, the researcher used seven parameters, they are new perception of customer, solemnity, openness of BM, reminding, motivating customerâs business, soving their problems and create a new business. From the test result of F analysis, it is explainable that four independent variables could be used to predict the dependent variable (increase of income), whereas the test result from t analysis indicated that the variable X3 (duration of office hour) has a significance influence to the increase of customerâs income. For others three variables, they have no influence to their income. One of mentoring quality variable (X2) which has an influence to it is the openness to the customer. From the result of paired samples t test, it indicated that there is a different income and shadaqa of the customer before and after following this program.